PENGARUH SISTEM APLIKASI ADMINSTRASI KEPENDUDUKAN DESA TERHADAP EFEKTIFITAS PELAYANAN ADMINISTRASI DESA PADA KANTOR DESA SUMBER SARI KECAMATAN SEBULU KABUPATEN KUTAI KARTANEGARA - toni nurhadi kumayza (Prodi Administrasi Negara FISIPOL Universitas Kutai Kartanegara, 2018)
village administration services are problematic such as requiring relatively long periods of time, dependence on certain administrative personnel, non-standard letter formats and poor records. The problem makes service ineffective. This happens because in providing administrative services still processed data applicants manually and do not use the application. In Sebulu sub district there is one village of Sumber Sari Village that has been using the application to provide services to its people since 2012 so we are interested to further examine how good and effective the application is to provide services. Keywords: application, public service